2016
DOI: 10.4103/2228-7477.181032
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency ultrasound time series signal analysis to evaluate high-intensity focused ultrasound lesion formation status in tissue

Abstract: High-intensity focused ultrasound (HIFU) is a novel treatment modality used by scientists and clinicians in the recent decades. This modality has had a great and significant success as a noninvasive surgery technique applicable in tissue ablation therapy and cancer treatment. In this study, radio frequency (RF) ultrasound signals were acquired and registered in three stages of before, during, and after HIFU exposures. Different features of RF time series signals including the sum of amplitude spectrum in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…With the development of nonlinear technology, many nonlinear computational methods are proposed to analyze various systems [23][24][25]. Researchers in the field of ultrasound have studied the characteristics of ultrasonic energy, sound speed, information entropy, and sample entropy of ultrasonic echo signals, hoping to find characteristics that can accurately reflect the characteristics of biological tissues [26][27][28][29][30]. In [26], the energy characteristics of ultrasonic signals were used to recognize the denatured biological tissue during HIFU treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of nonlinear technology, many nonlinear computational methods are proposed to analyze various systems [23][24][25]. Researchers in the field of ultrasound have studied the characteristics of ultrasonic energy, sound speed, information entropy, and sample entropy of ultrasonic echo signals, hoping to find characteristics that can accurately reflect the characteristics of biological tissues [26][27][28][29][30]. In [26], the energy characteristics of ultrasonic signals were used to recognize the denatured biological tissue during HIFU treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In [28,29], the biological tissue state after HIFU irradiation was assessed by the information entropy of the radio frequency ultrasound. In [30], the sample entropy of the radio frequency ultrasonic signals was employed to distinguish the normal porcine tissues and denatured porcine tissues. However, all the methods mentioned above have some disadvantages, such as sound speed measurement of biological tissues is easily affected by environmental noise, which leads to the inaccuracy of the recognition results of denatured biological tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there was a big difference between the Shannon entropy value of the ultrasonic signal of the normal biological tissues and the damaged biological tissues. In [19], the multi-scale sample entropy (MSE) of the radio frequency ultrasonic signals was employed to monitor the damage of porcine tissues. Compared with the Shannon entropy and MSE mentioned above, multi-scale permutation entropy (MPE) has the advantages including strong noise resistance and robustness, so the MPE is often employed to analyze the complexity of ultrasonic time series [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In [ 23 , 24 ], values of acoustic absorption and sound velocity were used to predict temperature rise and estimate treatment. In [ 25 , 26 ], biological tissue state after HIFU irradiation was assessed by information entropy of the radio frequency ultrasound. Comparing with ultrasonic attenuation, sound velocity, and information entropy, multiscale permutation entropy (MPE) can analyze sequence information more efficiently.…”
Section: Introductionmentioning
confidence: 99%